2023
DOI: 10.3390/v15091900
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Modeling of Aedes and Culex Mosquitoes: A Risk Map for Chikungunya and West Nile Viruses in Zambia

Rachel Milomba Velu,
Geoffrey Kwenda,
Samuel Bosomprah
et al.

Abstract: The circulation of both West Nile Virus (WNV) and Chikungunya Virus (CHIKV) in humans and animals, coupled with a favorable tropical climate for mosquito proliferation in Zambia, call for the need for a better understanding of the ecological and epidemiological factors that govern their transmission dynamics in this region. This study aimed to examine the contribution of climatic variables to the distribution of Culex and Aedes mosquito species, which are potential vectors of CHIKV, WNV, and other arboviruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, caution is needed in attributing these shifts solely to global climate change, as local factors like land use, urbanization, and atmospheric circulation patterns may contribute [ 28 31 ]. Similarly, observed precipitation changes in Tuvalu, China, and South Korea signify localised variations, impacting vector habitats and malaria transmission [ 12 , 14 ]. While trends align with global climate change expectations, distinguishing global contributions from regional influences requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, caution is needed in attributing these shifts solely to global climate change, as local factors like land use, urbanization, and atmospheric circulation patterns may contribute [ 28 31 ]. Similarly, observed precipitation changes in Tuvalu, China, and South Korea signify localised variations, impacting vector habitats and malaria transmission [ 12 , 14 ]. While trends align with global climate change expectations, distinguishing global contributions from regional influences requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review predicted that further increasing temperatures would extend the seasonality of malaria transmission, enabling it to occur for up to six months annually in 2051–80 in European countries [ 11 ]. A modelling study showed that increased temperature variations were related to higher probabilities of Aedes species’ occurrence, and the optimal occurrence would take place when the temperature variations from the mean were above 25°C [ 12 ]. Conversely, a previous observational study found a negative relationship between temperature and malaria incidence rate, with a sharp decrease in incidence rate during 2000–03 and 2012–14, respectively, occurring with increasing average temperatures in Ghana and Nigeria [ 13 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using the MaxEnt model to speculate the potential habitats of creatures has the characteristics of small distortion and good stability (Zheng et al., 2021 ). It has a wide range of applications and plays an important role in the study of the impacts of climate change on species distribution and the management and conservation of endangered species, involving a wide range of disciplines such as agronomy (Ali et al., 2023 ), forestry (Yousaf et al., 2022 ), virology (Velu et al., 2023 ; Zakharova et al., 2020 ), etc.…”
Section: Introductionmentioning
confidence: 99%